Effects of carrageenan edible coating systems on the browning behavior of minimally processed yacon - Tiburcio, Dolly Pearl C.; Rumbaoa, Rowena Grace O. (2009.)
ABSTRACT Kappa (κ) and iota (ɭ) carrageenan, with or without citric acid (CA), at 0.3% and 0.5%, were used as coating materials to inhibit or minimize enzymatic browning in minimally processed yacon (MPY). The antibrowning activity of the different coating materials were compared in terms of browning rates (Δ/hr). A sensory color acceptability evaluation using the Hedonic Scale was conducted by a 15-member consumer panel. Kinetics of color degradation in terms of their order of reaction, and reaction rate constants were determined. Browning rate in MPY held at 26°C for 24 hours and at 6°C for 168 hours tended to increase with time. κ- or ɭ-Carrageenan alone at the level used in this study inhibited browning rate in MPY. κ-Carrageenan alone has a bleaching effect on MPY; ɭ-Carrageenan has no bleaching effect. Combining citric acid with carrageenan generally resulted to a positive net effect in terms of browning inhibition which is more pronounced at 6°C. Increasing CA from 0.3% to 0.5% has no added benefit in preventing browning. The ratings of the sensory color evaluation were not consistent with the results of the objective color evaluation.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tubers -- Philippines; Yacon